Recovery of Li, Ni, Co and Mn from spent lithium-ion batteries assisted by organic acids: Process optimization and leaching mechanism - Ren, Liuyi; Liu, Bo; Bao, Shenxu; Ding, Wei; Zhang, Yimin; Hou, Xiaochuan; Lin, Chao; Chen, Bo (International journal of minerals, metallurgy and materials, 2024)
The proper recycling of spent lithium-ion batteries (LIBs) can promote the recovery and utilization of valuable resources, while also negative environmental effects resulting from the presence of toxic and hazardous substances. In this study, a new environmentally friendly hydro-metallurgical process was proposed for leaching lithium (Li), nickel (Ni), cobalt (Co), and manganese (Mn) from spent LIBs using sulfuric acid with citric acid as a reductant. The effects of the concentration of sulfuric acid, the leaching temperature, the leaching time, the solid–liquid ratio, and the reducing agent dosage on the leaching behavior of the above elements were investigated. Key parameters were optimized using response surface methodology (RSM) to maximize the recovery of metals from spent LIBs. The maximum recovery efficiencies of Li, Ni, Co, and Mn can reach 99.08%, 98.76%, 98.33%, and 97.63%. under the optimized conditions (the sulfuric acid concentration was 1.16 mol/L, the citric acid dosage was 15wt%, the solid–liquid ratio was 40 g/L, and the temperature was 83°C for 120 min), respectively. It was found that in the collaborative leaching process of sulfuric acid and citric acid, the citric acid initially provided strong reducing CO 2 ·− , and the transition metal ions in the high state underwent a reduction reaction to produce transition metal ions in the low state. Additionally, citric acid can also act as a proton donor and chelate with lower-priced transition metal ions, thus speeding up the dissolution process.